Effect of tortuosity on transport properties of mixed granular beds - Mota, M. (2000)
The properties of binary mixed beds were investigated in a wide range of the particle size ratio δ . The relationship between tortuosity T, porosity ε, δ , and volume fraction of the large particle x_D in mixtures was analysed. Disregarding the tortuosity increase for the range of dense packing led to error in the permeability and diffusivity calculation. The tortuosity variation in the mixed beds must be taken into consideration for modelling transport phenomena in granular mixed beds as well as for building porous media with pre-selected properties. A model of the mixed bed porosity and tortuosity is proposed. The maximum packing tortuosity can be calculated as the product of monosized packing tortuosity both for large and small particle fractions.